2020
DOI: 10.1186/s43044-020-00054-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of QRS fragmentation in 12-lead surface ECG in prediction of isolated epicardial coronary artery ectasia and its anatomical distribution in patients without acute coronary syndromes

Abstract: Background: Coronary artery ectasia (CAE) is a form of abnormal coronary artery lumen dilatation associated with epicardial flow disturbances and microvascular dysfunction. QRS complex fragmentation (fQRS) in surface ECG is caused by abnormal depolarization due to myocardial ischemia and scarring. It has been proved in different studies to be positively correlated with adverse cardiac events. This study aimed to assess the role of fQRS as a noninvasive predictor of CAE and its anatomical distribution. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These are also well-known risk factors for the development of CAD. Moreover, Kamal et al also found in their study that male gender was frequent in patients with CAE and an independent risk factor for CAE development [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are also well-known risk factors for the development of CAD. Moreover, Kamal et al also found in their study that male gender was frequent in patients with CAE and an independent risk factor for CAE development [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CAE may more frequently suffer angina, myocardial infarction, and cardiovascular mortality 11,12 . CAE is also correlated with fragmented QRS and QTc dispersion 13,14 . Patients with CAT may suffer from angina, accompanied by ST‐segment changes in exercise tests 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the presence of fQRS on a routine electrocardiogram (ECG) can give a reasonable indicator for the severity of cardiac involvement in different cardiac and/or systemic diseases (4) . Two-dimensional speckle tracking echocardiography (2D-STE) is a relatively new introduced method, which enable more reliable and complete myocardial function assessment by obtaining the myocardial strain and strain rates in the longitudinal, radial and circumferential directions based on the tracking of speckles in gray scale two-dimensional (2D) echocardiographic images (5) .…”
Section: Introductionmentioning
confidence: 99%